Ethnobotanical knowledge of diversity and utilization of plants among Dayak Lundayeh in Malinau, North Kalimantan, Indonesia - Ajiningrum, Purity Sabila; Munawaroh, Esti; Oktaviani, Dian; Saparita, Rachmini; Hewindati, Yuni Tri; Purwanto, Yohanes; Cahyaningsih, Ria (Ethnobotany Research and Applications, 2025)
Background: Indonesia’s rapid economic expansion has led to biodiversity loss, causing issues for ethnic groups like the Dayak Lundayeh in Kalimantan. As one of Indonesia’s oldest tribes, the Dayak Lundayeh are strongly committed to protecting natural resources and hold rich yet under-documented local knowledge. This study explores their expertise in spatial planning, plant species diversity, and plant uses while evaluating the economic value of non-timber forest products (NTFPs). Methods: The study was performed using qualitative and quantitative methods, including the Index of Cultural Significance (ICS) and Local User’s Value Index. Results: The Dayak Lundayeh organize their property into residential, production, resource reserve, and natural sections, showing great environmental awareness. They recognize 486 plant species for health, food, technology, building, and energy. The LUVI and ICS identify community-valued species, reflecting their everyday reliance on them. Harvesting and processing NTFPs are important in their livelihoods, integrating traditional practices with sustainable resource management. Conclusions: The findings emphasize the importance of integrating the Dayak Lundayeh’s social, socioeconomic, and ecological knowledge into regional development initiatives. Their ethnobotanical knowledge of plant diversity and utilization helps protect biodiversity and enables people in the area to cope with economic changes by promoting the sustainable management of plant resources. Keywords: Dayak Lundayeh, Ethnobotany, Ethnoecology, Local knowledge, Malinau